Maintaining Banking Asset Quality Through Investor Sentiment: Evidence From KBMI 3 Banks In Indonesia - Widy Muchamad; Dedi Supiyadi; Arus Reka Prasetia; Wufron Wufron; Ahmad Mudzakir (Journal of Business and Management Inaba, 2026)
This paper investigates the transmission mechanism through which capital structure decisions shape bank credit quality, with investor sentiment serving as the mediating channel. Drawing on a balanced panel of 11 KBMI 3-classified commercial banks listed on the Indonesia Stock Exchange over the 2021–2025 post-pandemic period, the study employs the Debt-to-Equity Ratio (DER), Price-to-Book Value (PBV), and Non-Performing Loan (NPL) as proxies for the respective constructs. The empirical strategy combines Random Effect Model (REM) estimation with bootstrap-resampling mediation analysis (5,000 iterations) to yield robust inference across 55 balanced observations. Estimation results show that DER does not exert a statistically significant direct influence on PBV, yet PBV demonstrates a significant inverse relationship with NPL. More importantly, the indirect effect of DER on NPL through PBV is statistically significant under bootstrap confidence intervals that exclude zero, confirming full mediation. The evidence points to market perception—captured by PBV—as the primary conduit through which funding-structure choices ultimately affect loan portfolio quality. Theoretically, the findings reconcile Signaling Theory, Trade-Off Theory, and Market Discipline Theory within a single mediating framework, enriching the literature on bank risk transmission in emerging economies. Practically, the results underscore the strategic value of cultivating positive investor sentiment as an indirect lever for reducing credit risk and reinforcing financial stability.